Acute mental health nursing : from acute concerns to the capable practitioner - Harrison, Mark; Howard, David; Mitchell, Damian (London : Sage, 2004)
This book is an introduction to acute mental health care. Contents include: acute psychiatric in-patient assessment; measuring health and social functioning using HoNOS; social inclusion and acute care; strategies for surviving acute care; case management: perspectives of the UK and US systems; integrated care pathways - the 'acute' context; risk assessment and management in acute mental health care; observation; cognitive behaviour therapy in in-patient care; psychosocial interventions; medication management.